Insights into the formation and mitigation of iodinated disinfection by-products during household cooking with Laminaria japonica (Haidai). (15th October 2022) - Wu, Menglin; Ding, Shunke; Cao, Zhongqi; Du, Zhenqi; Tang, Yuyang; Chen, Xiaoyan; Chu, Wenhai
Highlights: Health risk of I-DBP exposure from household cooking with Haidai was overlooked. I-DBPs formed from simulated household cooking with Haidai reached to mg/L level. Factors affecting I-DBP formation from household cooking with Haidai were ascertained. The high temperature of cooking played a decisive role in facilitating I-DBP formation. The soak of Haidai before cooking for food preparation inhibited I-DBP formation. Abstract: Iodinated disinfection by-products (I-DBPs) have attracted extensive interests because of their higher cytotoxicity and genotoxicity than their chlorinated and brominated analogues. Our recent studies have firstly demonstrated that cooking with seaweed salt could enhance the formation of I-DBPs with several tens of μg/L level. Here, I-DBP formation and mitigation from the reaction of disinfectant with Laminaria japonica (Haidai), an edible seaweed with highest iodine content, upon simulated household cooking process was systematically investigated. The total iodine content in Haidai ranged from 4.6 mg-I/g-Haidai to 10.0 mg-I/g-Haidai, and more than 90% of iodine is soluble iodide. During simulated cooking, the presence of disinfectant simultaneously decreased iodide by 15.0–32.8% to 2.7–5.8 mg/L and increased total organic iodine by 1.3–10.9 times to 0.5–1.8 mg/L in Haidai soup, proving I-DBP formation. The concentrations of iodinated trihalomethanes and haloacetic acids were at the levels of several hundreds of μg/L and several μg/L, respectively, which are 2–3 orders and 1–2 orders of magnitude more than those in drinking water. Effects of key factors including disinfectant specie, disinfectant dose, temperature and time on I-DBP formation were also ascertained, and temperature and disinfectant specie played a decisive role in the formation and speciation of I-DBPs. In order to avoid the potential health risk from the exposure of I-DBPs in Haidai soup, it is prerequisite to soak and wash dry Haidai sample over 30.0 min before cooking, which could effectively remove major soluble iodide. In general, this study provided the new insight into I-DBP formation from daily household cooking with Haidai and the corresponding enlightenment for inhabitants to eat Haidai in daily life. Graphical abstract: Image, graphical abstract